A Rare Case of Fibrosing Obliterative Appendicitis in a Young Patient: Case Report - Mohamed Arsath Shamsudeen; Peh Kiam Heng; G. Krishnaswamy; Mohamad Zahin Hafiz Zulkiple; Suresh V Chinni, (Malaysian Journal of Science (MJS), 2025)
Fibrosing obliterative appendicitis is an uncommon inflammatory condition of the appendix that can lead to significant diagnostic challenges, particularly in younger patients. In a patient presenting with abdominal pain at the emergency department, appendicitis must be considered and ruled out. However, due to various causes of abdominal pain, the diagnosis of appendicitis may be challenging. Therefore, thorough history taking and a careful clinical examination are essential for identifying appendicitis and ensuring prompt treatment. This study describes a young patient who presented with a complaint of right lower abdominal pain for the past 4 days. A 14-year-old male presented to the emergency department with right lower abdominal pain, without associated symptoms. He had a similar episode three months earlier and was treated conservatively. Ultrasound suggested mesenteric lymphadenitis. Diagnostic laparoscopy was initially performed, but was then converted to open surgery due to an invisible appendix. The procedure revealed an inflamed, slender appendix adhering to the cecum with enlarged mesenteric lymph nodes. Appendectomy and lymph node excision were performed. Histopathology confirmed fibrosing obliterative appendicitis with reactive lymphadenitis. The patient was discharged after two days in stable condition. This case highlights the diagnostic challenge of chronic appendicitis in paediatric patients. Diagnostic laparoscopy proved valuable in identifying fibrosing obliterative appendicitis, allowing for effective surgical intervention.